Energy efficient primary atomization of viscous food oils using an electrostatic method. (November 2018) - Vesely, P.W.; Schick, R.J.; Shrimpton, J.S.; Mashayek, F.
Abstract: Food oil coating applications typically require spraying with relatively viscous liquids. Traditional spray methods can by inefficient, requiring a large amount of energy to produce a uniform coating and/or producing a significant degree of overspray. The electrostatic charge injection atomization technique is shown to be appropriate for these viscous and dielectric food oils, where an additional electrical power of ≈ 0.1 W is required. Electrical performance data and also spray imaging and quantitative drop size measurement using phase Doppler interferometry are presented for atomizer orifice diameters of 150 and 250 μ m and liquid injection velocities of 10 m/s. The typical average drop diameter is typically 70% of the orifice diameter. The results show the atomization performance is independent of liquid viscosity over a viscosity range of factor 50.